MALE GENDER ROLE MESSAGES PADA TOKOH "HERO" DALAM EPISODE "CAHAYA HATI" DI PROGRAM "ZERO TO HERO" METRO TV - Hidayat, Nisa Imawati (Informasi, 2015)
AbstractThe research purpose is to determine how the television documentary producer "Zero to Hero" program on Metro TV classify male gender role messages in the cast of "hero" in that program. Researcher used social semiotics method Theo van Leeuwen with multimodal analysis procedure and 24 of male gender role theories from Ian M. Harris, that have been categorized into 5 classification: standard bearers, lovers, workers, bosses and rugged individuals. The result of this study revealed that the television documentary producer "Zero to Hero" program, construct the male gender role messages in the cast of "hero" to the category of male gender role messages consist with standard bearers, lovers, bosses and workers, who shows a positive image and dominant as a man who lived in patriarchal culture in Indonesia.AbstrakTujuanpenelitianiniuntukmengetahui bagaimana produsen program dokumenter televisi "Zero to Hero" di Metro TV mengklasifikasikan male gender role messages pada tokoh "hero" di dalam program tersebut. Peneliti menggunakan metode semiotika sosial Theo van Leeuwen dengan prosedur analisis multimodality dan teori 24 male gender role messages Ian M. Harris yang dikategorikan dalam 5 klasifikasi yaitu standar bearers, lovers, workers, bossesdan rugged individuals. Hasil penelitian ini mengungkapkan bahwa produsen program menampilkan tokoh "hero" dengan kategori male gender rolemessages berupastandar bearers, lovers, bosses dan workers yang menunjukkan citra positif dan dominan sebagaimana layaknya pria berperilaku dalam budaya patriaki di Indonesia.Keywords: Male Gender Role Messages, Hero, Documentary